The Investigation of the Effects of Banana Maturity on the Drying Kinetics of Thinly-Sliced Saba (Musa balbasiana) Using Hot-Air Dryer - Lola Domnina Pestaño; John Paul Bautista; Reizl Leguiab; Sean Danielle Puri (New Approaches in Engineering Research Vol. 16, 2021)
Banana is one of the top produced crops in the Philippines, and among its cultivars is the Musa balbasiana, commonly known as Saba. Due to its high moisture content, Saba is perishable and one of the methods to increase its shelf-life is drying. Because of its shelf life, it must be consumed a few days after harvest. The shelf life of Saba can be extended up to six months when dried to 12% moisture content. The research focuses on the effect of banana maturity and choses a mathematical model which will best fit its drying kinetics. The banana samples, the unripe and ripe Saba, were bone-dried without pre-treatment using a hot-air tray drier. To produce repeatable data, three trials were done for temperatures 40oC, 50oC and 60oC. Among the three mathematical models used in the study, the treated data for both unripe and ripe Saba best fit the Laplace Transform Model. Using Lagrange interpolation, the time per trial was computed; unripe Saba dried at 50oC achieved the ideal moisture content in an average time of 87.5574 minutes for the three trials while that of ripe Saba dried at 40oC achieved the same moisture content in an average time of 88.8619 minutes for the three trials. With the increase in temperature, the discoloration decreased indicating an enzymatic character of browning. The difference in the moisture that can be removed from Saba has a greater factor as compared to the temperature in determining the drying time.